Treatment of Epstein Barr virus-induced haemophagocytic lymphohistiocytosis with rituximab-containing chemo-immunotherapeutic regimens - Chellapandian, DeepakBabu (2013)
Haemophagocytic lymphohistiocytosis (HLH) is a life threatening complication of Epstein-Barr virus (EBV) infection. The anti-CD20 antibody rituximab depletes B cells, leading to improved outcomes for patients with EBV-associated B-lymphoproliferative disorders. To gather data on the use of rituximab in EBV-HLH, we performed a retrospective investigation involving 42 EBV-HLH patients who had received treatment with rituximab-containing regimens. On average, patients received 3 rituximab infusions (range 1 – 10) at a median dose of 375 mg/m(2). In all patients, rituximab was administered with other HLH-directed medications, including steroids, etoposide and/or ciclosporin. Rituximab-containing regimens appeared well tolerated and improved clinical status in 43% of patients. Examination of laboratory data obtained prior to and within 2 – 4 weeks after the first rituximab dose revealed significant reductions in EBV load (median load pre-rituximab: 114,200 copies/ml, median post-rituximab: 225 copies/ml, p=0.0001) and serum ferritin levels (median ferritin pre-rituximab: 4,260 μg/l, median post-rituximab: 1,149 μg/l, p=0.001). Thus, when combined with conventional HLH-directed therapies, rituximab improves symptoms, reduces viral load and diminishes inflammation. These data support the incorporation of rituximab into future prospective clinical trials for patients with EBV-HLH.